Increase in marine POM related to the presence of microplastic beads in a mesocosm experiment - Luisa Galgani; Manolis Tsapakis; Paraskevi Pitta; Anastasia Tsiola; Eleni Tzempelikou; Ionna Kalantzi; Chiara Esposito; Arturo Loiselle; Anastasia Tsotskou; Snezana Zivanovic; Eleni Dafnomili; Santi Diliberto; et al. (PANGAEA, 2020)
This dataset supports the recent publication "Microplastics increase the marine production of particulate forms of organic matter" by L. Galgani et al (2019) in ERL. It comprises all data presented in the manuscript and Supplementary Information. In the file, Control = mesocosm without plastic addition (1,2,3) and MP = mesocosm with plastic addition (1,2,3). The data proceed from the MESO-Plastic experiment in 2017 conducted at the Hellenic Center for Marine Research, a member of the European Aquacosm network of mesocosm facilities.
Supplement to: Galgani, Luisa; Tsapakis, Manolis; Tsiola, Anastasia; Tzempelikou, Eleni; Kalantzi, Ionna; Esposito, Chiara; Loiselle, Arturo; Tsotskou, Anastasia; Zivanovic, Snezana; Dafnomili, Eleni; Diliberto, Santi; Mylona, Kyriaki; Magiopoulos, Iordanis; Zeri, Christina; Pitta, Elli; Loiselle, Steven Arthur (2019): Microplastics increase the marine production of particulate forms of organic matter. Environmental Research Letters, 14(12), 124085, https://doi.org/10.1088/1748-9326/ab59ca